2022
DOI: 10.1093/europace/euac049
|View full text |Cite|
|
Sign up to set email alerts
|

Randomized comparison of atrioventricular node re-entry tachycardia and atrial flutter catheter ablation with and without fluoroscopic guidance: ZeroFluoro study

Abstract: Background Interventional cardiology procedures may expose patients and staff to considerable radiation doses. We aimed to assess whether exposure to ionizing radiation during catheter ablation of supraventricular tachycardia (SVT) can be completely avoided. Methods In this prospective randomized study, patients with SVT (atrioventricular re-entrant tachycardia n = 94, typical atrial flutter n = 29) were randomly assigned in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In recent years, the use of EAMSs as an alternative visualization technique in electrophysiology procedures has gained popularity due to its potential to decrease procedural time and reduce or even completely eliminate radiation exposure. Numerous studies have confirmed the feasibility of near-zero and zero-fluoroscopy approaches for CTI ablation, including their successful application as an extension to pulmonary vein isolation procedures within a single session (5,(15)(16)(17)(18)(19)(20)(21)(22)(23). In addition, the advent of visualizable steerable sheaths has yielded significant advancements in mitigating radiation exposure during catheter ablation procedures (24).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In recent years, the use of EAMSs as an alternative visualization technique in electrophysiology procedures has gained popularity due to its potential to decrease procedural time and reduce or even completely eliminate radiation exposure. Numerous studies have confirmed the feasibility of near-zero and zero-fluoroscopy approaches for CTI ablation, including their successful application as an extension to pulmonary vein isolation procedures within a single session (5,(15)(16)(17)(18)(19)(20)(21)(22)(23). In addition, the advent of visualizable steerable sheaths has yielded significant advancements in mitigating radiation exposure during catheter ablation procedures (24).…”
Section: Discussionmentioning
confidence: 97%
“…The utilization of 3D electroanatomical mapping systems (EAMS) during ablation procedures for typical flutter has resulted in a significant reduction in exposure to fluoroscopy ( 4 , 9 , 10 ). Recent researches have demonstrated that it is feasible to perform fluoroscopy-free ablation procedures for typical flutter with the guidance of EAMS ( 5 , 6 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Catheter ablation in the treatment of SVT in adults using non-fluoroscopic mapping systems such as the EnSite system has been reproducibly found to be feasible, safe and effective. [19][20][21][22][23][24][25]…”
Section: Open Accessmentioning
confidence: 99%
“…A parallel comparison in a multicentric registry study of outcomes from a zero-fluoroscopy approach and conventional fluoroscopy approach in the treatment of SVT showed similar ablation and procedure times and comparable success rates in excess of 98% 18. Catheter ablation in the treatment of SVT in adults using non-fluoroscopic mapping systems such as the EnSite system has been reproducibly found to be feasible, safe and effective 19–25…”
Section: Introductionmentioning
confidence: 96%